Serum Immunoglobulin G of Neuro‑Behçet’s Disease Patients Reduce Cerebral Expression Levels of Survival Pathway Factors - (:unkn) unknown (My University, 2020)
Objective: Anti‑neuronal antibodies are found in sera of neuro‑Behçet’s disease (NBD) patients. In this study, our aim was to analyze the potential mechanisms by which NBD immunoglobulin (Ig) Gs affect neuronal dysfunction. Materials and Methods: Purified IgGs obtained from pooled sera of six each NBD patients and healthy controls (HCs) were administered to Sprague Dawley rats through intraventricular injection. Control rats received phosphate‑buffered saline (PBS) only. Locomotor activity was assessed by open field test on days 0, 10, and 25. Cerebral expression levels of intracellular pathway factors associated with cell survival and viability were measured by real‑time polymerase chain reaction. Results: Rats treated with NBD IgG exhibited reduced motor activity. On day 25, the mean number of crossings was 44 ± 7, 90 ± 12, and 93 ± 5 and the mean number of rearings was 18 ± 7, 34 ± 5, and 35 ± 6 for NBD IgG, HC IgG, and PBS groups, respectively (P < 0.001). Relative expression levels of Akt‑1 (0.4 ± 0.2, 1.0 ± 0.3, and 0.9 ± 0.6; P = 0.004), DJ‑1 (0.6 ± 0.2, 1.0 ± 0.6, and 0.9 ± 0.5; P = 0.047),mouse double mininute‑2 (0.5 ± 0.3, 0.9 ± 0.2, and 1.0 ± 0.2; P = 0.002), andmechanistic target of rapamycin (0.4 ± 0.2, 0.8 ± 0.4, and 0.9 ± 0.6; P = 0.006)were significantly lower in NBD‑IgG group than HC IgG and PBS groups. By contrast, the expression levels of factors associated with apoptosis (caspase 3,mitochondrial carrier homolog 1, and B‑cell lymphoma‑2) were comparableamong different treatment arms. Conclusion: Our results suggest that at least a fraction of NBD IgG interacts with neuronal surface antigens and subsequently decreases neuronal viability through Akt pathway inhibition. By contrast, NBD IgG does not appear to activate neuronal apoptosis. Further identification of the binding sites of serum IgG ıs required.